All Trans Retinoic Acid Regulates Expression of Genes Invoved in Cell Senescence Pathway in Gastric Cancer Cell Line MKN45 - Luu, Thi Binh (H. : ĐHQGHN, 2020)
Cellular senescence is a state in wich cells can not longer divide. The dysregulation of the cell senescence signaling pathway could lead to uncontrolled cell proliferation and formation of malignant cells. Intervening in cell senessence signaling pathway to bring cancer cells back to cell senessence state is a potential way in cancertreatment. Recent studies show that tumor cells can undergo celluar senessencestate by using special chemotherapy. In this study, we indicatedthat All trans retinoic acid (ATRA) is able to influence the expression of genes involved in cell senessence signaling pathway in gastric cancer cells MKN45. ATRA down-regulatesthe expression of important genes controlling cell growth. On the other hand, ATRA up-regulate the expression of GADD45A, P21 and P53 genes that play an important role in the signaling pathway of cells.This finding suggestes that ATRA could inhibite MKN45 cells through activating cell senescence signaling pathway